KOALISI NEGARA TELUK DIAM ATAS PELANGGARAN HAK ASASI MANUSIA KEPADA IKHWANUL MUSLIMIN PASCA KUDETA MILITER 2013 DI MESIR - Jadug Trimulyo Ainul Amri; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This research aims to explain and analyze responses from the Gulf Cooperation Council towards the violation of human rights in Egypt post-military coup d'etat in 2013. Democracy comes with a high price in Egypt. However in 2012, a presidential election was held for the very first time in the history of the Egyptian state establishment where Mohamed Morsi was elected as a head of state. Mursi came from Freedom and Justice Party, a political party founded by Ikhwanul Muslimin. After the first year of his incumbent, Morsi was overthrown through a military coup led by General Abdul Fattah Al Sisi in 2013. This event caused a political crisis in Egypt, demonstrations emerged within the entire country and received repressive responses from the military regime. Thousands of people were killed, imprisoned and executed without a fair trial. The international community has condemned the human rights violation that was occurring however, the Gulf countries such as Saudi Arabia, Uni Emirat Arab, Bahrain, Kuwait, and Oman tended to turn a blind eye towards this issue. In fact, supportive responses were shown towards the ruling regime with Qatar as the only country with an opposite response. As a result, Ikhwanul Muslimin was banned in almost the entire Middle Eastern region.